Psychological and Environmental Factors for Older Adults to Exercise: A Systematic Review - Martín-Moya, Ricardo; Jesús Ruiz-Montero, Pedro; Rivera García, Enrique; Leeson, George (Revista de Psicología del Deporte (Journal of Sport Psychology), 2020)
Research investigation concerning potential motivators and psychological influences on health and physical exercise participation have increased worldwide in the last two decades. In contrast, few investigations have analysed this phenomenon in older people living in different contexts. Older adults suffer a notable diminution of physical functions that may be followed by psychological disorders and are detrimental to their affective and social relationships. Therefore, it is of great importance to find strategies that increase the participation of older adults’ in regular exercise. A systematic review of 945 studies was conducted. All of the 27 studies reviewed, that met the inclusion criteria, have undertaken mixed-method, qualitative and qualitative approaches. The data were extracted based on the following variables: the methodology and the instrument/questionnaire used, the type of article, number of participants, duration and intensity of the interventions, profile of the older adults, most relevant findings and the country where the study was developed. The instruments used in the studies, were mainly semi-structured interviews, discussion groups and questionnaires, focusing mainly on the United States and Canada. The knowledge of psychological and environmental factors is a key aspect relevant to both the social and physical aspects and has a strong influence on older people’s commitment to exercise, influencing their wellbeing. The aim of this study was to explore barriers and facilitators of adherence to a physical exercise programme for older adults.